2014
DOI: 10.1007/s00264-014-2497-5
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, randomised, controlled multicentre study comparing cervical disc replacement with anterior cervical decompression and fusion

Abstract: Although ACDF may increase the risk of additional surgery, clinical outcomes indicated that both Mobi-C artificial cervical disc replacement and ACDF were reliable. Radiographic data showed that ROM of the cervical spine, FSU angle and treated and adjacent segments were relatively better reconstructed and maintained in the Mobi-C group compared with those in the ACDF group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 22 publications
2
35
0
Order By: Relevance
“…Compared with anterior cervical discectomy and fusion, the cervical disc arthroplasty offers the theoretical biomechanical advantage of preservation of motion at the index level, which reduces stresses at the adjacent levels [12,13]. The equivalency or superiority of the cervical disc arthroplasty as an alternative to anterior cervical discectomy and fusion has been seen in FDA Investigational Device Exemption and other studies [5,7,8,10,22,30,32,34,35,37,38,[42][43][44]. However, there is controversy regarding whether the cervical disc arthroplasty results in a lower frequency of reoperation compared with the anterior cervical discectomy and fusion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Compared with anterior cervical discectomy and fusion, the cervical disc arthroplasty offers the theoretical biomechanical advantage of preservation of motion at the index level, which reduces stresses at the adjacent levels [12,13]. The equivalency or superiority of the cervical disc arthroplasty as an alternative to anterior cervical discectomy and fusion has been seen in FDA Investigational Device Exemption and other studies [5,7,8,10,22,30,32,34,35,37,38,[42][43][44]. However, there is controversy regarding whether the cervical disc arthroplasty results in a lower frequency of reoperation compared with the anterior cervical discectomy and fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Supplemental material is available with the online version of CORR 1 .). Finally, 12 eligible RCTs were included in our systematic review and meta-analysis [5,8,10,22,30,34,35,37,38,[42][43][44]. The study selection is shown in the PRISMA flowchart (Fig.…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…All eight studies were rated as “low risk of bias” according to the Cochrane Back Review Group criteria. One study [ 59 ] failed to clearly report adequate randomization and only one study provided the information of allocation concealment [ 59 ]. Blinding of patients, surgeons, and assessors were not considered achieved because of the nature of the studies and evident difference of implant design.…”
Section: Resultsmentioning
confidence: 99%